Adolescent Involvement in Sports Activities and Internalisation of Moral Values - Enrika Kromerova; Saulius Šukys (Lithuanian Sports University, 2018)
Background.  Relatively  little  knowledge  is  available  to  date  about  moral  values  among  adolescents.  As participation  in  sports  activities  may  contribute  to  positive  youth  development,  this  study  aims  to  examine  the relations between adolescents' involvement in sports activities and the internalisation of their moral values. We assessed this relationship with respect to gender as well. Methods.  The  sample  included  385  adolescents  (192  girls  and  193  boys)  between  13  to  16  years  of  age   (M age = 14.6, SD =1.11); 43.4% (n = 167) of the research participants were involved in competitive sports. The studied adolescents had participated in their respective sport for an average of 2.97 (SD = 1.12) years. The internalisation of moral values was assessed using the 24-item adolescent-report Moral Values Internalisation Questionnaire (Hardy, Padilla-Walker, & Carlo, 2008). Four forms of value regulation were assessed (external, introjected, identified and integrated). Overall value internalisation was also evaluated. Results. Significant differences were found between adolescent involvement in sports activities and external regulation (p < .05), introjected regulation (p < .01), identified regulation (p < .05) as well as integrated regulation   (p  <  .01).  In  depth  analyses  showed  that  the  four  forms  of  value  regulations  were  higher  for  the  athletes  with experience up to three years and tended to be lower in the group of athletes with higher sports experience. The same relationship was established in the sample of boys, but not in that of girls. Conclusions.  The  research  results  demonstrated  that  the  identified  regulation  manifested  more  than  other regulations did (external, introjected and integrated). Adolescent athletes possessed higher points of moral value internalisation  in  all  regulations  than  adolescent  non-athletes.  Nevertherless,  referring  to  sports  experience,  the internalisation forms of moral values of adolescent athletes with more than the three-year sport experience did not differ in comparison with those of adolescent non-athletes. Research results show that the internalisation of moral values for adolescents with higher sports experience is lower compared to that of adolescents with lower sports experience. Keywords:  adolescents' moral values, participation in sport, sports experience.